Design of an Expert System for Early Diagnosis of Dental and Oral Diseases Using the Web-Based Forward Chaining Method - Yohanes Bowo Widodo (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Teeth and mouth are important organs. Diseases that attack the teeth can cause bad effects, such as appearance and health problems. In general, people only undergo examinations at the dental clinic after serious problems with their teeth occur. This has an impact on the handling and treatment of patients. If the condition of tooth decay is already severe, usually extra treatment is carried out by a doctor, such as carrying out tooth extraction surgery. Expert systems are a branch of computer science that can be applied in the medical field, in this case dentistry. This research aims to produce a web-based expert system for early diagnosis of dental and oral diseases. This research has succeeded in creating an expert system for early diagnosis of dental and oral diseases, so that it can help the public to find out about the dental and oral diseases they are suffering from. The knowledge base of this expert system is made in the form of if-then rules. The inference method used is Forward Chaining. The results of the questionnaire show that the level of acceptance of the application among users is very good, namely 90.48%. Based on the results of these tests, it can be concluded that the expert system application that has been created can be recommended for use by the public as a tool for early diagnosis of dental and oral diseases.